Influence of coal ash on the concrete properties and its performance under sulphate and chloride conditions - Putra Jaya, Ramadhansyah; Mangi, Sajjad Ali; Mohd Haziman, Wan Ibrahim; Norwati, Jamaluddin; Khahro, Shabir Hussain (Springer, 2021)
This study investigated the influence of Coal Bottom Ash (CBA) on the concrete properties and evaluate the effects of combined exposure of sulphate and chloride conditions on the concrete containing CBA. During concrete mixing, cement was replaced with CBA by 10% of cement weight. Initially, concrete samples were kept in normal water for 28 days. Next, the specimens were moved to combined solution of 5% Sodium sulphate (Na2SO4) and 5% sodium chloride (NaCl) solution for further 28 to 180 days. The experimental findings demonstrated that the concrete containing 10% CBA (M2) gives 12% higher compressive strength than the water cured normal concrete (M1). However, when it was exposed to solution of 5% Na2SO4 and 5% NaCl, gives 0.2% greater compressive strength with reference to M1. The presence of 10% CBA decreases the chloride penetration and drying shrinkage around 33.6% and 29.2% respectively at 180 days. Hence, this study declared 10% CBA as optimum that can be used for future research.